Carboxyl-Terminal Residues N478 and V479 Required for the Cytolytic Activity of Listeriolysin O Play a Critical Role in Listeria monocytogenes Pathogenicity - Cheng, Changyong; Jiang, Li; Ma, Tiantian; Wang, Hang; Han, Xiao; Sun, Jing; Yang, Yongchun; Chen, Zhongwei; Yu, Huifei; Hang, Yi; Liu, Fengdan; Wang, Bosen; et al. (Frontiers in Immunology, 2017)
Listeria monocytogenes is a facultative intracellular pathogen that secretes the cytolysin listeriolysin O (LLO), which enables the bacteria to cross the phagosomal membrane. Listeria monocytogenes regulates LLO activity in the phagosome and minimizes its activity in the host cytosol. Mutants that fail to compartmentalize LLO activity are cytotoxic and have attenuated virulence. Here, we showed that residues N478 and V479 of LLO are required for LLO hemolytic activity and bacterial virulence. A single N478A mutation (LLON478A) significantly increased the hemolytic activity of LLO at a neutral pH, while no difference was observed at the optimum acidic pH, compared with wild-type LLO. Conversely, the mutant LLOV479A exhibited lower hemolytic activity at the acidic pH, but not at the neutral pH. The double mutant LLON478AV479A showed a greater decrease in hemolytic activity at both the acidic and neutral pHs. Interestingly, strains producing LLON478A or LLOV479A lysed erythrocytes similarly to the wild-type strain. Surprisingly, bacteria secreting LLON478AV479A had barely detectable hemolytic activity, but exhibited host cell cytotoxicity, escaped from the phagosome, grew intracellularly, and spread cell-to-cell with the same efficiency as the wild-type strain, but were highly attenuated in virulence in mice. These data demonstrate that these two residues are required for LLO hemolytic activity and pathogenicity in mice, but not for escape from the phagosome and cell-to-cell spreading. The finding that the nearly non-hemolytic LLON478AV479A mutant grew intracellularly indicates that mutagenesis of a virulence determinant is a novel approach for the development of live vaccine strains.